Embracing a 'new normal': the construction of biographical renewal in young adults' narratives of living with a stoma. Issue 2 (27th September 2019) - Polidano, Kay; Chew‐Graham, Carolyn A.; Bartlam, Bernadette; Farmer, Adam D.; Saunders, Benjamin
Abstract: Stoma surgery can be a life‐changing procedure due to bodily changes and related psychological responses. Despite previous literature identifying unique challenges for young adults living with a long‐term condition, no studies have explored the biographical implications of stoma formation. Drawing on interviews with 13 young adults, aged 18–29 years, with a stoma resulting from inflammatory bowel disease, this article aims to generate new theoretical insights in understanding the process of biographical (re)construction and the wider implications of stoma formation among this group. Data analysis combined constructivist grounded theory and narrative analysis. Whilst two narratives display 'biographical suspension' characterised by a distancing of self from their stoma, the majority of narratives highlight positive transformations in the young adults' conceptions of self; which we explain through the concept of 'biographical renewal'. The liberating effects of stoma surgery allowed young adults to reclaim aspects of their pre‐illness selves, yet also reconfigure a new, altered sense of self, culminating in a 'new normal'. However, psychological distress also co‐existed alongside these positive representations, revealing a tension that young adults attempt to reconcile through narrativising their experiences. Our findings have implications for the identification and management of the psychological needs of young people with a stoma.